Characterization of wide bandgap power semiconductor devices - Wang, Fei; Zhang, Zheyu; Jones, Edward A. (Institution of Engineering and Technology, 2018)
This book is an authoritative overview of Wide Bandgap (WBG) device characterization providing essential tools to assist the reader in performing both static and dynamic characterization of WBG devices, particularly those based on using silicon carbide (SiC) and gallium nitride (GaN) power semiconductors.
Keywords: Wide gap semiconductors.; Power semiconductors.; Electric capacity.; elektronické knihy; electronic books